Avaliação da adesão ao controle da transmissão vertical do HIV entre mães atendidas em maternidade de referência do Estado do Pará - SOUZA, Lívia Layany Ferreira de (2023)
Introduction: the increase in the number of AIDS cases among women has lead to an increase in the maternal-infant transmission of human acquired immunodeficiency virus. The vertical transmission of HIV may occur during pregnancy, the labor and by breastfeeding. Most of cases of Transmission of HIV from mother to child, occur in Peri-partum period, due to contact with blood and contaminated maternal secretions. Nowadays, the rate of the vertical transmission of HIV, without any intervention, is approximately 25%, however, a lot of studies published in literature demonstrates to a reduction for levels between zero and 2% with the use of antiretroviral therapy during the pregnancy and delivery, elective cesarean section, in select cases, use of AZT for neonate and contraindication for breastfeeding. Objective: 1) To evaluate realization of prophylaxis of the vertical transmission of HIV, in pregnant women, during the prenatal, and in the delivery assistance on the motherhood; 2) Establish comparisons between the mothers who had serological diagnosis on the delivary occasion, and ones who Knew your serological diagnosis previously, with respect to procedures for the reduction the risk of infection in newborns; 3) To evaluate the epidemiological profile of the mothers who joined less the prophylaxis treatment currently recommended. 4) To assess the result of the prophylaxis of vertical transmission of the HIV in children (seroconvertion or serorrevertion). Method: Retrospective study of 103 HIV infected pregnant women, admitted in the FSCMPA, for the delivery assistance in the period of January on the December 2006. The pregnant women were divided into two groups: group A, knew your positive serology for the HIV virus on on the motherhood, during hospitalization for childbirth, and group B knew your serological diagnosis previously (during prenatal or Prior to pregnancy). Results: Among the HIV-infected women 84,5% of pregnants were in the B group and 15.5% in the A group. 89,7% among the mothers of the B group, used zidovudina (AZT) during the pregnancy. Among the mothers who frequented specializaded treatment unities only 33,3% of A group and 60% of B group remained assiduous. The serorrevertion was confirmed in 16.7% of the children in B group . Among the mothers who had not sought the units of reference (16/103), 75% were single; 62,5% were of interland; 50% had done prenatal complete; Conclusion: mothers who had serological diagnosis at the time of birth, were ones who less adhered to prophylaxis of vertical transmission.